Invasive cardiopulmonary exercise testing in the evaluation of unexplained dyspnea: Insights from a multidisciplinary dyspnea center. (29th August 2020) - Huang, Wei; Resch, Stephen; Oliveira, Rudolf KF; Cockrill, Barbara A; Systrom, David M; Waxman, Aaron B
Abstract: Background: Unexplained dyspnea is a common diagnosis that often results in repeated diagnostic testing and even delayed treatments while a determination of the cause is being investigated. Through a retrospective study, we evaluated the diagnostic efficacy of a multidisciplinary dyspnea evaluation center (MDEC) using invasive cardiopulmonary exercise test to diagnose potential causes of unexplained dyspnea. Methods: We reviewed the medical records of all patients referred with unexplained dyspnea to the MDEC between March 2011 and October 2014. We assessed the diagnostic efficacy before and after presentation to the MDEC. Results: During the study period a total of 864 patients were referred to the MDEC and, of those, 530 patients underwent further investigation with invasive cardiopulmonary exercise test and constituted the study sample. The median age was 57 (44–68) years, 67.2% were women, and median body mass index was 26.22 (22.78–31.01). A diagnosis was made in 530 patients including: exercise pulmonary arterial hypertension of 88 (16.6%), heart failure with preserved ejection fraction of 94 (17.7%), dysautonomia 112 (21.1%), oxidative myopathy of 130 (24.5%), primary hyperventilation of 43 (8.1%), and other 58 (10.9%). The time from initial presentation to referral was significantly longer than time to diagnosis after referral for non-standardized conventional methods versus diagnosis through MDEC using invasive cardiopulmonary exercise test (511 days (292–1095 days) vs . 27 days (13–53 days), p < 0.0001). In a subgroup analysis, we reviewed that patients referred from cardiovascular clinics were more likely to have a greater number of diagnostic tests performed and, conversely, patients referred from pulmonary clinics were more likely to have a greater number of treatments prescribed before referral to MDEC. Conclusions: As a result of this retrospective study, we have evaluated that a multidisciplinary approach that includes invasive cardiopulmonary exercise test dramatically reduces the time to diagnosis compared with traditional treatment and testing methods.